2017
DOI: 10.1371/journal.pone.0175214
|View full text |Cite
|
Sign up to set email alerts
|

The role of subcutaneous adipose tissue in supporting the copper balance in rats with a chronic deficiency in holo-ceruloplasmin

Abstract: We have previously shown that (1) an acute deficiency in blood serum holo-ceruloplasmin (Cp) developed in rats that were fed fodder containing silver ions (Ag-fodder) for one month and (2) the deficiency in holo-Cp was compensated by non-hepatic holo-Cp synthesis in rats that were chronically fed Ag-fodder for 6 months (Ag-rats). The purpose of the present study is to identify the organ(s) that compensate for the hepatic holo-Cp deficiency in the circulation. This study was performed on rats that were fed Ag-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The system that ensures the copper turnover in the body comprises an intracellular system that provides the synthesis of cuproenzymes, including secretory ones (Figure 1), and an extracellular system that controls the copper balance in the whole organism [66]. A key player of extracellular copper metabolism is Cp, which indicates the current state of copper homeostasis and corresponds to the physiological requirements of various organs with copper [63,[67][68][69][70]. Cp, a representative example of a "moonlighting" protein, is the major extracellular copper-containing protein in vertebrates [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The system that ensures the copper turnover in the body comprises an intracellular system that provides the synthesis of cuproenzymes, including secretory ones (Figure 1), and an extracellular system that controls the copper balance in the whole organism [66]. A key player of extracellular copper metabolism is Cp, which indicates the current state of copper homeostasis and corresponds to the physiological requirements of various organs with copper [63,[67][68][69][70]. Cp, a representative example of a "moonlighting" protein, is the major extracellular copper-containing protein in vertebrates [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo pulse-chase experiments revealed that de novo synthesis of [ 14 C]Cp in Ag-fed animals occurred even when the liver was isolated from the bloodstream [65]. It turned out that this Cp was synthesized and excreted by the cells of subcutaneous adipose tissue, to which silver was not delivered [160]. Thus, the silver helped to uncover the interorgan control mechanism that supports copper balance in the blood and compensates for the deficit of oxidase Cp.…”
Section: Interplay Between Silver and Pathways Driving Intracellulmentioning
confidence: 99%
“…In liver cells, Ag( i ) ions are erroneously inserted in the active sites of the forming Cp of the blood serum, which contain cysteine residues and can coordinate Cu( i )/Ag( i ) ions. 38,63,91 The resulting Cp variant is enzymatically inactive, so the serum copper concentration and Cp oxidase activity decrease, while the Cp protein concentration remains the same (Fig. 8B, C and D).…”
Section: Discussionmentioning
confidence: 97%